The fair trade boom: an analysis of baby boomers’ knowledge, attitudes, behaviors, and barriers pertaining to fair trade - Benson, Ebony L. (Kansas State University, 2012)
Purchasing fair trade products is a form of socially responsible consumption. Fair trade is founded on the idea of paying fair wages and providing safe working environments to marginalized producers, typically from developing countries. Baby Boomers, the generational cohort that is the focus of this study, were born between the years 1946 and 1964. The purpose of this thesis is to expand the knowledge base of fair trade consumption related to the Baby Boomer generation. This study makes a positive contribution towards this goal by furthering the understanding of Baby Boomers knowledge about and attitudes towards the fair trade movement, as well as assessing their current level of engagement in purchasing of fair trade products and their perceptions about barriers to purchasing fair trade products to a greater degree. An additional contribution made by this study is the comparison of differences in fair trade knowledge, attitudes, and behaviors of Early versus Late Baby Boomers—a new contribution to the body of knowledge on fair trade. Altogether, 168 Baby Boomers (63 Late Boomers and 105 Early Baby Boomers) participated in the study. Data were collected through an online questionnaire. Questions in the questionnaire focused on: 1) knowledge of the fair trade movement; 2) attitudes about the fair trade movement; 3) fair trade purchasing behaviors; and 4) perceived barriers to fair trade purchasing. Data analysis included a combination of both quantitative (descriptive statistics, independent samples t-tests, and correlation analysis) and qualitative techniques. Guagnano, Stern, and Dietz’s (1995) ABC Model framed the study and Rogers (1983) diffusion theory and the prerequisites for adoption of an innovation guided conceptualization of the barriers to fair trade purchasing. Overall, findings of the study indicated that the participants were knowledgeable about the fair trade movement. They also exhibited positive attitudes towards fair trade but were not willing to compromise on certain product characteristics. The participants were somewhat engaged in a number of fair trade purchasing behaviors and they perceived numerous barriers to purchasing fair trade products. Finally, there were no identifiable differences between the Early and Late Baby Boomers in terms of knowledge, attitudes, or behaviors.
Keywords: Fair trade; Baby boomers; Marketing (0338)